THE INFLUENCE OF DEBT TO ASSET AND RETURN ON ASSET TOWARD TAX AVOIDANCE ON FOOD AND BEVERAGES COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Frinan Satria; Edrik Tantheo (Journal of Accounting and Management Innovation, 2023)
This study was conducted to see whether there is an effect of Debt to Assets and Return on Assets on tax avoidance. The sample used in this study uses companies engaged in the food and beverage sector and listed on the Indonesia Stock Exchange in 2019-2021. In this study, the authors used a population that came from companies engaged in the food and beverage sector and listed on the Indonesia Stock Exchange in 2019-2021. The method used to determine the sample using purposive sampling with a total sample obtained as many as 21 companies with a time period used is 3 years so that the total sample of companies obtained is 63 company samples. The results of this study were conducted to analyze the effect of debt to assets and return on assets on tax avoidance in companies engaged in the food and beverage sector listed on the Indonesia Stock Exchange. This study uses the SPSS 26 application and uses descriptive statistics, classical assumption test, multiple linear regression analysis and hypothesis methods. The results of this study indicate that Debt to Assets has no significant effect on Tax Avoidance while Return on Assets does not significantly affect Tax Avoidance. But when doing the F Test, the results obtained, namely Debt to Assets and Return on Assets have an effect on Tax Avoidance.